Water, climate change and uncertainty in the Great Lakes and Rio Grande/Bravo Regions. Issue 3 (10th February 2023) - Bassone-Quashie, Yena; VanNijnatten, Debora; Johns, Carolyn
Abstract: Uncertainty is inherent in transboundary water governance, yet climate change is deepening the uncertainties faced by those who manage shared water resources. This paper identifies and assesses uncertainties in the transboundary water governance context by applying an analytical framework which integrates insights from the uncertainty, adaptive governance, and public policy literatures to analyze policy documents in two complex transboundary cases: the Great Lakes and Rio Grande/Bravo basins. Findings from the analysis indicate that: first, deep uncertainties exist in both cases but the two basins face different combinations of, and interactions between, uncertainties; second, the system of scarcity assessed in this analysis (the Rio Grande/Bravo Basin) indicates more conflict-based uncertainties which aggravate natural and technical system uncertainties; and third, the governance system itself is a significant source of uncertainty, or exacerbates existing uncertainties, in both basins. The case studies reveal that governance systems need to focus on different sources, types and levels of uncertainty, and that policy responses need to be designed to move to a 'monitor-and-adapt' governance approach to reflect different uncertainties across systems of abundance and scarcity. An analysis of the preparedness of governance systems to respond and adapt to uncertainties is also needed and highly recommended. HIGHLIGHTS: Develops and applies a framework for characterizing uncertainties in climate-impacted water basins. Demonstrates the ways in which different water basins face unique combinations of uncertainties. Discusses the utility of moving to a 'monitor-and-adapt' water management approach. Sets out a research agenda for linking uncertainties with concrete governance mechanisms. Graphical Abstract